Assessing Volatile Organic Compounds (VOCs) in a laboratory and office building environment - Hector Garcia-Gonzalez; Maria Teresa Lopez-Pola; Rafael Rodriguez; Pilar Fernandez-Rubio; Pablo Fernandez-Rodriguez (Air Quality, Atmosphere & Health, 2025)

Wavelet analysis and sinusoidal modelling of environmental variables in a weaned piglet farm - Maria D. Fernandez; Manuel R. Rodriguez; Xose R. Fdez-Vidal; Roberto Besteiro (Building and Environment, 2025)

Promoting Workplace Health, Safety, and Well-Being Among Essential Agricultural Workers Through Vaccine-Preventable Infectious Diseases Training in the Rio Grande Valley - Anabel Rodriguez; David I Douphrate; Ana L Pineda Reyes; Susana Zavala; Andrea V. Cabrera Cruz; Maria D Alegria; Brian Ukaegbu; Annie J Keeney; Brenda Berumen-Flucker; Eva M Shipp; Shannon P Guillot-Wright; Maria E Fernandez-Esquer; et al. (Journal of Agromedicine, 2025)

Unraveling autonomic cardiovascular control complexity during orthostatic stress: Insights from a mathematical model - Martin Miranda Hurtado; Rafael Kaempfer; Justen R. Geddes; Mette S. Olufsen; Maria Rodriguez-Fernandez (Mathematical Biosciences, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Ataxia-telangiectasia in Latin America: clinical features, immunodeficiency, and mortality in a multicenter study - Renan A. Pereira; Ellen O. Dantas; Jessica Loekmanwidjaja; Juliana T. L. Mazzucchelli; Carolina S. Aranda; Maria E. G. Serrano; Elisabeth A. De La Cruz Córdoba; Liliana Bezrodnik; Ileana Moreira; Janaira F. S. Ferreira; Vera M. Dantas; Valéria S. F. Sales; et al. (Immunologic Research, 2024)

Fruit juice and childhood obesity: a review of epidemiologic studies - Junichi R. Sakaki; Nancy R. Rodriguez; Maria-Luz Fernandez; Michael J. Puglisi; Ming-Hui Chen; Ock K. Chun (Critical Reviews in Food Science and Nutrition, 2023)

Muscular carnosine is a marker for cardiorespiratory fitness and cardiometabolic risk factors in men with type 1 diabetes - Laura Brugnara; Ana Isabel García; Serafín Murillo; Josep Ribalta; Guerau Fernandez; Susanna Marquez; Miguel Angel Rodriguez; Maria Vinaixa; Núria Amigó; Xavier Correig; Susana Kalko; Jaume Pomes; et al. (European Journal of Applied Physiology, 2022)

Minimum temperature and evapotranspiration in Central Amazonian floodplains limit tree growth of Nectandra amazonum (Lauraceae) - Janaína Quixabeira Gonçalves; Flávia Machado Durgante; Florian Wittmann; Maria Teresa Fernandez Piedade; Daigard Ricardo Ortega Rodriguez; Mário Tomazello-Filho; Pia Parolin; Jochen Schöngart (Trees, 2021)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

Long-Term Mangiferin Extract Treatment Improves Central Pathology and Cognitive Deficits in APP/PS1 Mice - Carmen Infante-Garcia; Juan Jose Ramos-Rodriguez; Irene Delgado-Olmos; Carlos Gamero-Carrasco; Maria Teresa Fernandez-Ponce; Lourdes Casas; Casimiro Mantell; Monica Garcia-Alloza (Molecular Neurobiology, 2017)

Triple-layered mixed co-culture model of RPE cells with neuroretina for evaluating the neuroprotective effects of adipose-MSCs - David Rodriguez-Crespo; Salvatore Di Lauro; Amar K. Singh; Maria T. Garcia-Gutierrez; Manuel Garrosa; J. Carlos Pastor; Ivan Fernandez-Bueno; Girish K. Srivastava (Cell and Tissue Research, 2014)

Role of cannabis and endocannabinoids in the genesis of schizophrenia - Emilio Fernandez-Espejo; Maria-Paz Viveros; Luis Núñez; Bart A. Ellenbroek; Fernando Rodriguez de Fonseca (Psychopharmacology, 2009)